Life scientist takes helm at MIT. - Applewhite, A. (IEEE spectrum)
This article announces the appointment of Susan Hockfield as the first woman to lead MIT and the first biologist to head the school. As a researcher, she primarily studied the development of the mammalian brain and anomalies in that process. She pioneered the use in brain research of monoclonal antibodies, exceptionally pure antibodies produced from cultured cells that have come to be widely used in diagnostics, immunization and research. Hockfield expressed a special interest in designing early education programs to stimulate children's enthusiasm for science and math, and she's committed to providing opportunities and building communities for women, minorities, and international students and scholars. Hockfield's approach was to promote improvements in the quality of campus life and the remuneration for graduate students.